Confirmatory factor analysis of latent constructs for measuring social well-being in African migrant samples - Ejoke, Ufuoma Patience; Du Plessis, Edwin Devon; Dev, Smitha; Al Bustami, Ghanem Jaser; Varghese, Mary (Elsevier Ltd, 2024)
The present study contributes to psychology and well-being literature by investigating social well-being in minority contexts. The factor structure of the Keyes' long format 33-item social well-being measure was investigated among African migrant samples. A cross-sectional survey methodology was used to collect data from a total of 404 African migrants living in South Africa (n = 146), Uganda (n = 158) and Kenya (n = 100). They were 202 (50%) males, 195 (48.3%) females, and 7 (1.7%) of the samples did not disclose their gender. They were aged from 14 to 70 with a Mean age of 32.21 (standard deviation = 7.696). Data collected were analysed using CFA in AMOS (version 29). We found an unstable four-factor emic solution for African migrants in Sub-Sahara Africa. We could not replicate the theoretical social well-being model of Keyes (1998) among African migrant samples in Sub-Saharan Africa. Insights from the study will be critical to designing culturally appropriate indigenous measures that accurately reflect the social realities and well-being constructs of African migrants. Our findings will also help policymakers and service providers to identify areas of need, develop appropriate socio-cultural programmes, and allocate resources more effectively to support the integration and well-being of migrants within African societies.
Keywords: African; migrants; ecosystem; Measurement; Social well-being